An update on the international network for acid prevention - Tremblay, G; Kelley, B; Davies, M (Mine Closure 2023: 16th International Conference on Mine Closure, 2023)
Mining activities include the extraction and processing of economic minerals as well as the movement and storage of the waste rock and tailings, some of which may be reactive producing Acid and Metalliferous Drainage (AMD). This can impact operations and lead to a high level of residual risk/liability at the cessation of mining which may delay or prevent effective closure and lease relinquishment. Responsible management of these reactive materials throughout the operational phase of mining and for the entirety of mine’s life cycle inclusive of post-closure is therefore critical for the mining industry´s current and future success. The International Network for Acid Prevention (INAP) is an international network of mining companies that was proactively formed by mine operators in 1998. Twenty-five years later, INAP continues to drive globally recognized leading practice in AMD risk management so that all mining companies can operate sustainably in their respective environments across the asset life cycle. This is achieved though mining industry-led collaboration, knowledge development, and sharing of outcomes. INAP programs and activities are focussed on the reduction and management of AMD and, as such, can greatly assist in minimising the issues around residual risk which may present as a major barrier to operational performance and achieving successful mine closure. As INAP enters its next 25-year period, a review of the Strategic Plan is currently underway to ensure that INAP continues to add value and deliver in emerging and strategic areas, particularly given the pace of change which the industry needs to embrace to remain viable and relevant. In addition to management of AMD, INAP has recently expanded its focus to thoroughly embrace prevention of AMD. In this presentation, examples of leading practices including source control work targeting the prevention and reduction of AMD, through better mine rock stockpile construction techniques will be presented. The paper will also consider how INAP is working to make the global ARD guide (GARD Guide) more effective and useful to all stakeholders worldwide, along with an update on current and future projects. INAP’s key role in bringing the global technical and regional ARD alliance together will also be briefly discussed.